2016
DOI: 10.1016/j.ebiom.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Complement and Antibody-mediated Enhancement of Red Blood Cell Invasion and Growth of Malaria Parasites

Abstract: Plasmodium falciparum malaria is a deadly pathogen. The invasion of red blood cells (RBCs) by merozoites is a target for vaccine development. Although anti-merozoite antibodies can block invasion in vitro, there is no efficacy in vivo. To explain this discrepancy we hypothesized that complement activation could enhance RBC invasion by binding to the complement receptor 1 (CR1). Here we show that a monoclonal antibody directed against the merozoite and human polyclonal IgG from merozoite vaccine recipients enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…Antibodies against the P. falciparum asparagine-rich protein enhance merozoite invasion of RBC in vitro (106). Merozoite-specific antibodies in conjunction with complement can also facilitate RBC invasion (107). Antibody-dependent enhancement of infection was also observed in vivo after immunization with a Plasmodium berghei parasite blood-stage preparation which led to increased death after challenge (108).…”
Section: Antibody-dependent Enhancement Of Infectionmentioning
confidence: 99%
“…Antibodies against the P. falciparum asparagine-rich protein enhance merozoite invasion of RBC in vitro (106). Merozoite-specific antibodies in conjunction with complement can also facilitate RBC invasion (107). Antibody-dependent enhancement of infection was also observed in vivo after immunization with a Plasmodium berghei parasite blood-stage preparation which led to increased death after challenge (108).…”
Section: Antibody-dependent Enhancement Of Infectionmentioning
confidence: 99%
“…Data was presented showing a reduced level of inhibition mediated by sera from MSP1-42 vaccinated malaria-naïve human subjects in C3/ C 4 supplemented serum compared to C3/ C 4 depleted serum. However, in non-vaccinated controls, there was no difference in invasion between complement active and complement inactivated sera, as would be expected if complement activated sera significantly enhanced invasion and if MSP1-42 C-terminal antibodies augmented this effect (Biryukov et al, 2016). Further, while Biryukov et al support their findings with in vivo animal models using P .…”
mentioning
confidence: 69%
“…While Biryukov et al propose that mouse monoclonal antibodies to MSP1-19 augment the enhancement effect of normal sera, the reported effect was only moderate when considering absolute parasitamias, and there appears to be large variability in the effect as seen across experimental replicates (data presented in the supplementary materials within Biryukov et al, 2016). Data was presented showing a reduced level of inhibition mediated by sera from MSP1-42 vaccinated malaria-naïve human subjects in C3/ C 4 supplemented serum compared to C3/ C 4 depleted serum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported the enhancing effects of anti -merozite antibodies and complement interactions at promoting red blood cell invasion and growth by merozoites. We have observed this enhancement using both a traditional invasion assay and the Plasmodium berghei ANKA model of experimental malaria (Biryukov et al, 2016). Our results are in contradiction to those reported by Boyle et al (Boyle et al, 2015) who found that in the presence of complement, anti -merozoite antibodies are effective in preventing RBC invasion.…”
mentioning
confidence: 94%